The effect of Five-Finger strategy on the holistic thinking of chemistry students in the second intermediate grade - Najwa Abdulmunem Jasim Alnoori (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The objective of the research is to identify the effect of the five-finger strategy on the holistic thinking of chemistry students in the second intermediate grade, where the sample consisted of 60 female students in a second classfrom one of the intermediate schools in Baghdad city, divided into two groups: control and experimental. The experimental design was based on the partial control; the scientific course was defined in the third and fourth chapters of the science book of the second intermediate grade.The two research tools were prepared: the attainment test with the scientific course and the holistic thinking scale paragraph (36) of multiple-choice pre- and posttest. The results showed a statistically significant difference between the two research groups in favor of the experimental group that followed the five-finger strategy with a significant effect.